Analiza skupień zorganizowanych grup przestępczych jako przykład zastosowania metod statystycznych w kryminologii - Porębski, Andrzej (Czasopismo Prawa Karnego i Nauk Penalnych, 2021)
The paper is a methodological study of the cluster analysis method enriched with an empirical example of its application to the study of organized crime. The paper provides a formal (mathematical) and informal description of hierarchical cluster analysis and considers the application of this method to the study of empirical data on organized crime groups. The empirical part originally used qualitative data on 14 organized crime groups, formalized in terms of six variables. Using cluster analysis, clusters of similar criminal groups were distinguished. The study shows that the cluster analysis method can effectively distinguish interpretable clusters of similar criminal groups.